Revitalisasi Potensi Wisata Desa Wisata Jurit Baru Melalui Program Promosi Kreatif Dan Pemberdayaan Masyarakat - Yahya Muhaimin; Dwi Retno Sulistyorini; Danisya Ira Asdi Putri; Wini Ken Sari; Nia Agustina; Muhamad Sulthan Hidayat; Nena Narwastu; Lalu Muhammad Rizki Suhardi; Emi Mastura; Riani Zati; I Wayan Gunada (Unram Journal of Community Service, 2023)
Jurit Baru Village is a village located in Pringgasela District, East Lombok Regency, which has potential natural resources to be used as tourist attractions and has been designated as a tourist village since 2021. Tourism potential in Jurit Village has not been managed optimally. This is due to the lack of promotion carried out by the local community. The purpose of the activity is to promote tourism potential in Jurit Baru Village on social media through Jurit Baru Tourism Village accounts (youtube) and @desawisata_juritbaru (instagram), and community empowerment as tourism supporters. Activities will be carried out from June to August 2023. The programs implemented include: tourism awareness counseling, content training and digital promotion, creating tourism village accounts, making promotional videos, and English fun. Results of activities: (1) The community becomes aware of the tourism potential in Jurit Baru Village and can maintain and manage existing tourist attractions. (2) People understand digital promotion strategies through content training and digital promotion. (3) The community has a forum to promote Tourism Villages through the Jurit Baru Tourism Village account (youtube) and @desawisata_juritbaru (instagram). (4) The community becomes aware of the existence and potential that exists in Jurit Baru Village through promotional videos. (5) Children in Jurit Baru Village can recognize English as a foreign language that is fun to learn and reduce the intensity of gadget use for children in Jurit Baru Village